Effect of Concomitant Use of Analgesics on Prognosis in Patients Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Mao, Ziyang; Jia, Xiaohui; Jiang, Panpan; Wang, Qinyang; Zhang, Yajuan; Li, Yanlin; Fu, Xiaolan; Jiao, Min; Jiang, Lili; Liu, Zhiyan; Guo, Hui (Frontiers in Immunology, 2022)
Background: Drug–drug interactions (DDI) pose new challenges beyond traditional pharmacodynamics in the context of optimizing the treatment options with immune checkpoint inhibitors (ICIs). To alleviate cancer-related pain, analgesics are of absolute vital importance as chronic medications used by cancer patients. However, the possible outcome of ICIs treatment concomitant with analgesics remains unclear. Methods: Original articles describing the possible influence of analgesics use on ICIs treatment published before 1 December 2021 were retrieved from PubMed, Embase, and the Cochrane Library. Odds ratio (OR) with 95% confidence interval (CI) for objective response rate (ORR), hazard ratio (HR) with 95% CI for progression-free survival (PFS) and overall survival (OS) were calculated using the random-effects or fixed-effects model, and heterogeneity was assessed using the χ2-based Q test. Publication bias was examined by funnel plot analysis. Results: A total of 11 studies involving 4404 patients were included. The pooled OR showed that opioids use decreased the response of opioids users to ICIs compared to non-opioids users (OR=0.49, 95% CI=0.37–0.65, P<0.001). Compared to patients who did not receive opioids, opioids users had an increased risk of progression and mortality (HR=1.61, 95% CI=1.37–1.89, P<0.001; HR=1.67, 95% CI =1.30–2.14, P<0.001, respectively). Furthermore, the concomitant use of non-steroidal anti-inflammatory drugs (NSAIDs) was not significantly associated with differences in ORR, PFS, and OS in patients treated with ICIs (OR=1.40, 95% CI=0.84–2.32, P=0.190; HR=0.90, 95% CI=0.77–1.06, P=0.186; HR=0.90, 95% CI=0.71–1.14, P=0.384, respectively). Conclusion: The concomitant use of opioids during ICIs treatment has an adverse effect on patient prognosis, while the use of NSAIDs is not significantly associated with the prognosis in patients treated with ICIs. Keywords: Immune checkpoint inhibitors; Analgesics; Drug–drug interactions; Prognosis; Meta-analysis.